2006
DOI: 10.1002/yd.194
|View full text |Cite
|
Sign up to set email alerts
|

Intentional youth programs: Taking theory to practice

Abstract: Intentionality, including a lived ethos of positive youth development, is the key to success in engaging young people in out‐of‐school learning experiences that meet their developmental needs and everyday interests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 3 publications
0
13
0
3
Order By: Relevance
“…Proper planning, securing staff buy-in and engagement beforehand, and incorporating sufficient resources and support were found to be critical factors separating those camps that successfully implemented Explore 30 and those that did not. The importance of programming with intention to achieve targeted results, as identified in this study, has been a clear trend in the camp and youth development literatures Mainieri & Anderson, 2014;Walker, 2006).…”
Section: Discussionmentioning
confidence: 90%
“…Proper planning, securing staff buy-in and engagement beforehand, and incorporating sufficient resources and support were found to be critical factors separating those camps that successfully implemented Explore 30 and those that did not. The importance of programming with intention to achieve targeted results, as identified in this study, has been a clear trend in the camp and youth development literatures Mainieri & Anderson, 2014;Walker, 2006).…”
Section: Discussionmentioning
confidence: 90%
“…Intentional and sustained programs yield the greatest and most diverse impacts (Walker, 2006), yet such continuity is difficult to sustain in many PYD settings. Alternatively, community programs focused on program quality and fidelity to research-based principles can show evidence of merit with reasonable inference to worth (Arnold, Braverman & Cater, 2016;Blyth, 2011).…”
Section: Implications For Practicementioning
confidence: 99%
“…41) where they develop supportive relationships with staff and other youth, try on new roles and identities (Konopka, 1973), learn new skills and explore new ideas and experiences. While the activities, venues and specific target outcomes vary greatly, high quality youth development programs can provide intentional, developmentally appropriate opportunities for young people to grow and develop that occur outside the formal school day (Blyth, 2006;Walker, 2006).…”
Section: Participationmentioning
confidence: 99%
“…Youth reap a wide range of positive developmental outcomes through participation, including physical health, positive psychosocial development, enhanced academic achievement, mastery of specific skills, reduction in violence and risk-taking behavior, and positive identity development (Bronfenbrenner, 1979;Eccles & Gootman, 2002;Pittman, Martin, & Williams, 2007;Resnick et al, 1997;Scales, Benson, Leffert, & Blyth, 2000;Scales & Leffert, 1998;Walker, 2006;Weiss, Little, & Bouffard, 2005;Zeldin, Camino & Calvert, 2007). Scales et al (2010) found that 15-year-olds who scored high on a relationships and opportunities index (measuring opportunities for participation and supportive relationships) were much more likely than low scorers to: work up to their ability at school (60% vs. 25%); have a grade point average of 3.5 or higher (73% vs. 53%); have a sense of purpose and hope for their future (59% vs. 17%); and have a positive sense of their ethnic identity (56% vs. 15%).…”
Section: Benefits Of Participationmentioning
confidence: 99%
See 1 more Smart Citation